Determinants of Private Landowner Participation in Endangered Species Conservation: A Comprehensive Review and Analytical Framework. Issue 7 (3rd July 2021) - Messick, Jared A.; Serenari, Christopher; Rubino, Elena C.
Abstract: A positive future for Endangered species hinges on proactive and positive relations between private landowners and agencies. However, the scattered literature investigating the determinants of private lands conservation suggests critical deficiencies, especially in the context of Endangered species conservation (ESC). Complete understandings of how private lands and ESC align and differ are required to pinpoint how to reverse negative trends. In this systematic review, we situate these literatures within environmental stewardship to clarify the drivers of landowner engagement in ESC. Our results revealed that individual obligations to conserve wildlife might be overridden by negative attitudes that are oriented and contextualized. We also reveal that future research will need to investigate how agencies can overcome critical resource and institutional shortfalls that impact landowner decision-making about the costs and benefits of ESC. Cultivating social capital seems promising, but it needs to be facilitated across landscapes and overcome ideological differences.